(untitled) (Eureka Journal of Humanities and Social Research, 2026)
This article analyzes the role of rational (cognitive) and irrational (emotional) factors in the formation of national mentality, as well as their correlation. It highlights the importance of logical thinking, knowledge, and experience alongside traditions, customs, emotions, and beliefs in the development of national consciousness and worldview. The study also demonstrates how rational and emotional elements are harmonized under the influence of social, cultural, and historical factors.